Improved outcomes after heart transplantation for cardiac amyloidosis in the modern era - Kristen, Arnt; Kreußer, Michael; Blum, Patrick; Schönland, Stefan; Frankenstein, Lutz; Dösch, Andreas; Knop, Benjamin; Helmschrott, Matthias; Schmack, Bastian; Ruhparwar, Arjang; Hegenbart, Ute; Katus, Hugo; et al. (The journal of heart and lung transplantation, 2018)
Background: Cardiac amyloidosis, caused most commonly by deposition of light chain (AL) or transthyretin (ATTR) type fibrils, has an extremely poor prognosis. In this retrospective single-center study, we evaluated temporal trends in survival after heart transplantation for cardiac amyloidosis. Methods: We analyzed 48 patients with cardiac amyloidosis (AL, n = 32; familial ATTR, n = 16) who underwent heart transplantation from May 2002 to March 2017. Patients were analysed in 2 periods, Era 1 (2002- 2007) and Era 2 (2008- 2017), separated by altered patient selection in both, AL and ATTR amyloidosis, and changed chemotherapy regimens for AL amyloidosis. Results: The modern era was characterized by a lower number of extracardiac organ involvement for AL (94% isolated cardiac amyloidosis in Era 2 vs 56% in Era 1; p = 0.0221), and more frequent treatment for AL with the proteasome inhibitor bortezomib (94% in Era 2 vs 6% in Era 1; p < 0.0001). AL patients had significantly lower survival than patients with non-amyloid cardiomyopathy after heart transplantation in Era 1, and ATTR patients had numerically lower survival. However, survival in the modern era was comparable to non-amyloid transplants in both cohorts, possibly reflecting a shift in chemotherapy strategies and patient selection, respectively. Conclusions: In the current era, use of enhanced chemotherapy regimens for isolated advanced AL cardiac amyloidosis was associated with outcomes comparable to non-amyloid cardiomyopathy. We conclude that heart transplantation in highly selected patients with isolated non-systemic advanced cardiac amyloidosis may be a feasible approach.
First published: 15 November 2017
Gesehen am 26.06.2018